Pesticide Residue Monitoring on Agriculture in Indonesia - Asep Nugraha Ardiwinata; Lin Nuriah Ginoga; Eman Sulaeman; Elisabeth Srihayu Harsanti (Jurnal Sumberdaya Lahan, 2018)
Abstract. Most agricultural producers use pesticides to prevent pests and increase yield and quality of the food they grow. Pesticides can damage people’s health, and lead to birth defects (teratogenic in character) and death in humans and animals. Many of these chemical residues, especially derivatives of organochlorine pesticides, demonstrate dangerous bioaccumulation levels in the body and environment. The problems caused by organochlorine residues (lindan, aldrin, dieldrin, endrin, heptachlor and DDT) on agricultural lands that are still found today are generally the consequence of past usage that dates back to the1960s. Research on pesticide residues in Indonesia was carried out several years ago by various research institutes and universities and some of these results were collected between 1985 and 2017. Data distribution of the results on pesticide residues include in Aceh, North Sumatra, West Sumatra, Jambi, Bengkulu, Lampung, Banten, Jakarta, West Java, Central Java, East Java, Yogyakarta, Bali, South Kalimantan, North Sulawesi, South Sulawesi, Gorontalo, Maluku, and Papua. Most of the pesticide residue research has been conducted on vegetables. Pesticide residues were found in various commodities and matrices such as rice, soybeans, cow's milk, chicken eggs, fruit ingredients, vegetables, soil, paddy water, river water, lake water, pond water, sea water, water birds, animal feed, fish, frogs, lamb, birds, eggs, tea, and honey. Pesticide residues found were insecticide (organochlorine, organophosphate, carbamate, pyrethroid), and fungicide (dimethomorp, fenobucarb, propineb, benomyl, carbendazim and thiametoxam). Organochlorine insecticides have been banned, but the residues are still found today. This is due to the nature of organochlorines which have high persistence properties. Even though insecticide residues (organophosphate, carbamate, pirethroid) found in food commodities are still below the maximum residual limit (MRL), namely SNI 7313: 2008, but some close to MRL. Particularly for organochlorine residues in soil, water and plants insecticides must be monitored because they are persistent, toxic and accumulative. This paper aims to review of pesticide residues in various products including food, and the potential impact of pesticide residues on human health. Abstrak. Sebagian besar produsen pertanian menggunakan pestisida untuk mencegah hama dan meningkatkan hasil dan kualitas makanan yang mereka tanam. Pestisida dapat merusak kesehatan manusia, dan bersifat teratogenik dan mematikan pada manusia dan hewan. Banyak dari residu kimia ini, terutama turunan pestisida organoklorin, menunjukkan tingkat bioakumulasi yang berbahaya dalam tubuh manusia dan lingkungan. Masalah tersebut disebabkan oleh residu organoklorin (lindan, aldrin, dieldrin, endrin, heptachlor dan DDT) yang digunakan sejak tahun 1960-an. Penelitian tentang residu pestisida di Indonesia dilakukan beberapa tahun yang lalu oleh berbagai lembaga penelitian dan universitas yang dikumpulkan antara tahun 1985 dan 2017. Distribusi data hasil residu pestisida tersebar di Aceh, Sumatera Utara, Sumatera Barat, Jambi, Bengkulu, Lampung, Banten, Jakarta, Jawa Barat, Jawa Tengah, Jawa Timur, Yogyakarta, Bali, Kalimantan Selatan, Sulawesi Utara dan Selatan, Gorontalo, Maluku, dan Papua. Penelitian yang telah dilakukan menemukan residu pestisida tidak hanya ditemukan di berbagai komoditas pertanian seperti beras, kedelai, susu sapi, telur ayam, bahan buah, sayuran tetapi juga pada tanah, sawah, air sungai, air danau, air kolam, air laut, burung air, pakan ternak, ikan, katak, domba, telur burung, teh, dan madu. Residu pestisida yang banyak ditemukan di lapangan adalah insektisida (organoklorin, organofosfat, karbamat, piretroid), dan fungisida (dimethomorp, fenobucarb, propineb, benomyl, carbendazim dan thiametoxam). Insektisida golongan organoklorin telah dilarang penggunaannya, namun residunya masih ditemukan hingga kini. Hal ini dikarenakan sifat organoklorin yang memiliki sifat persistensi yang tinggi. Residu insektisida (organofosfat, karbamat, piretroid) yang ditemukan di dalam komoditas pangan secara umum masih di bawah batas maksimum residu (BMR) yang mengacu pada standar nasional, yaitu SNI 7313: 2008, namun beberapa residu insektisida telah mendekati BMR. Khusus untuk residu insektisida golongan organoklorin di dalam tanah, air dan tanaman harus dipantau karena sifatnya yang persisten, beracun, dan akumulatif. Makalah ini bertujuan untuk mengkaji residu pestisida dalam berbagai produk termasuk makanan, dan dampak potensial residu pestisida pada kesehatan manusia.